Curcumin suppresses gastric cancer by inhibiting gastrin‐mediated acid secretion. Issue 8 (21st June 2017) - Zhou, Shufen; Yao, Dongjie; Guo, Ling; Teng, Ling
Abstract : Hyperacidity in the stomach is known to promote the progression of gastric cancer. The plant‐derived chemotherapeutic curcumin is used to treat gastric cancer. The objective of this study was to investigate whether curcumin regulates gastrin‐mediated acid secretion in suppressing gastric cancer. Gastric cancer cells were treated with 25 μm curcumin, followed by Annexin V/propidium iodide double‐staining assay to evaluate cell apoptosis. Western blot analysis was used to analyze caspase‐3 expression in response to curcumin treatment. Gastrin levels in culture medium were also monitored. Mice bearing gastric cancers were treated with curcumin, followed by analysis of tumor caspase‐3 expression, gastric acid pH, and gastric secretion in serum. Curcumin prominently inhibited gastric cancer cell proliferation and promoted cell apoptosis. Caspase‐3 was upregulated by curcumin treatment. Curcumin also reduced gastrin secretion. Curcumin dramatically inhibited tumor growth, increased gastric pH, and reduced gastric secretion. In gastric cancer, curcumin suppresses gastrin‐mediated acid secretion, which inhibits gastric cancer progression. Abstract : Curcumin is used to treat gastric cancer, but its mode of action in not fully understood. In this study, we investigated whether curcumin regulates gastrin‐mediated acid secretion. Curcumin treatment was shown to inhibit gastrin secretion, and thus increase gastric pH. Curcumin also prominently inhibited gastric cancer cell proliferation and promoted cell apoptosis.